THE EFFECTIVENESS OF TAMSULOSIN, SOLIFENACIN, AND COMBINATIONS THERAPY TAMSULOSIN ADDED SOLIFENACIN ON LOWER URINARY TRACT SYMPTOMS AFTER DOUBLE J STENT INSERTION - Pramana, Ida Bagus Putra; Rizaldi, Fikri; Djojodimedjo, Tarmono (Indonesian Urological Association, 2019)
Objective: Insertion of DJ Stent is a procedure that is often done by urologist. Insertion of DJ Stent can cause LUTS complaints and greatly affect the physical and psychosocial health of patients. The aim of this study was to determine the effectiveness difference of tamsulosin therapy 0.4 mg/day, solifenacin 5 mg/day and the combination of tamsulosin therapy 0.4 mg/day added solifenacin 5 mg/day to manage LUTS complaint after DJ Stent insertion. Material & Methods: This study was a randomized placebo-controlled trial. There were 4 groups, group I received placebo, group II received tamsulosin 0.4 mg/day, group III received solifenacin 5 mg/day, and group IV received combination therapy of tamsulosin 0.4 mg/day added solifenacin 5 mg/day. Evaluation based on International Prostatic Symptom Score (IPSS) and Ureteral Stent Symptom Questioner (USSQ) score. Data were analyzed using SPSS 21.0. It is said to be significant if p<0.05. Results: There were a total of 32 samples consist of 19 (59.3%) men and 13 (40.6%) women. There were significant improvements in the score of total IPSS, IPSS storage and IPSS quality of life score in patients who received combination therapy (p<0.05) when compared with patients who received monotherapy. The highest decrease in USSQ scores 1, 2, 3, 4, 5 and 6 were in the group that received combination therapy when compared with the monotherapy group. Conclusion: The combination therapy is safe and effective to improve IPSS total, IPSS storage and IPSS Quality of Life scores compared with monotherapy.